2004
DOI: 10.1300/j045v18n03_02
|View full text |Cite
|
Sign up to set email alerts
|

Women's Priorities for Lay Health Home Visitors

Abstract: While racial, ethnic, and socioeconomic health disparities in maternal and child health persist among women, few studies describe experiences of low-income women during pregnancy. We undertook a qualitative study of women's self-reported experiences with home visitors to gain understanding of priorities for participation and service delivery. Lay health home visitors provided satisfactory services and maintained close relationships with their clients. The mother-to-mother relationship is critical in facilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These data support other work that found that strong patient-provider relationships that are characterized by good communication during encounters are particularly important in vulnerable populations. 2831 …”
Section: Discussionmentioning
confidence: 99%
“…These data support other work that found that strong patient-provider relationships that are characterized by good communication during encounters are particularly important in vulnerable populations. 2831 …”
Section: Discussionmentioning
confidence: 99%
“…However, providers’ attitudes and lack of compassion influence patients and their care experiences in negative ways. BIPOC patients often report feeling disvalued and not heard and having difficulties working with providers who do not understand their cultures and are not aware of power dynamics [ 6 , 47 , 48 ]. Because this study only included providers and the majority of our participants were white, it is possible that subtle discrimination or negative patient-provider interactions based on race (not LEP) were under-reported.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they have demonstrated abilities to improve maternal and child health and developmental outcomes in the context of home visiting (McNaughton, 2004). Alternatively, CHWs have an authentic presence grounded in life experiences similar to those of their clients, and may be able to reach women who have difficulty forming relationships, are fearful of professionals, experience language or cultural barriers to care, or are engaged in risk behaviors (Sheppard, Williams, & Richardson, 2004). CHWs provide intensive, relationship‐based social support using peer role modeling and empowerment strategies to address chronic stressors and basic needs, increase access to resources, encourage positive health behaviors, and help engage and maintain women in services.…”
Section: Interventionsmentioning
confidence: 99%